The autonomy dilemma: territoriality and identity in the Miskito-Sandinista conflict - Schubmann, Lena (Diálogos Latinoamericanos, 2018)
This paper explores the emergence of conflict between the Miskito and the Nicaraguan Sandinista government in the early years after the overthrow of the Somoza dictatorship. Outlining the polarisation of the debate in the late 1980s between supporters and opponents of the Sandinistas and their views of its revolutionary project and noting the lack of agency attributed to the Miskito themselves in these arguments, the article rejects arguments centred around race or ideology as an explanation for the conflict. Instead, use is made of Kate Crehan’s development of Gramscian analysis to explore the contrasting meanings ascribed to notions of territoriality and autonomy in public statements by Miskito and Sandinista leadership in the early 1980s.